Giving Incentives and the Impact on the Discipline of Economic Teachers in Implementing Their Assignment - Dicki Hartanto; Mia Anggelia Syafitri (Perspektif Pendidikan dan Keguruan, 2021)
This study aims to determine the effect of giving incentives to the discipline of economics teachers in carrying out assignments at SMA Negeri 12 Pekanbaru. The population is 8 teachers, because the population is small, the authors make the population as a sample. Data collection techniques that the author uses are questionnaires, interviews, and documentation. And the data processing technique that the author uses is a simple linear regression formula and product moment correlation with the help of the SPSS version 16.0 program. Based on the presentation and analysis of the data, it is known that the provision of incentives has a significant effect on the discipline of economics teachers in carrying out their duties at SMA Negeri 12 Pekanbaru. This is evidenced by the results of the analysis that observation = 0.938 is greater than Rtable at a significant level of 5% (0.838 > 0.707) this means that Ha is accepted, Ho is rejected. ro observation = 0.938 is greater than Rtable at a significant level of 1% (0.938 > 0.834) This means that Ha is accepted, Ho is rejected. Thus it can be concluded that there is a significant effect between the provision of incentives on the discipline of economics teachers in carrying out their duties of 0.881 X 100% = 88.1%.